Analysis of air safety in the European system of air traffic - Луппо, О.Є.; Лазоренко, В.А. (Proceedings of National Aviation University (archive), 2008)
Article describes air traffic safety provision requirements in the Air Traffic Management system of Europe. Consideration of air traffic variation which affecting the air traffic management operations have been reviewed.